Production of slow release potassium silicate fertilizer using the internal heat type fluidized bed reactor a plant design - Balbin, Anie Lyn L.; Chua, Christopher M.; Layug, Jose Genaro R.; Santos, Ruel F. (Quezon City College of Engineering, 1996)
Product: 0-0-20 Slow-release potassium silicate fertilizer -- Plant location: Malolos, Bulacan -- Annual volume of production: 6,000 MT -- Annual gross sales: Php 180,000,000 -- Annual income: Php 6,037,010 -- Total capital investment: Php 100,175,095 -- Product unit cost: Php 23.55/kg -- Product selling price: Php 30.00/kg -- Payback period: 7.33 years -- Return on investment: 6.05% -- Break-even capacity: 4,550 MT/year
Submitted in partial fulfillment of the requirements in ChE 142 Plant Design.
Keywords: Factories -- Design and construction; Potassium fertilizers; Fluidized reactors